Computer-Assisted Design Template Guided Percutaneous Radiofrequency Thermocoagulation through Foramen Rotundum for Treatment of Isolated V2 Trigeminal Neuralgia: A Retrospective Case-Control Study - Ran Wang; Ying Han; Lijuan Lu (Pain Research and Management)
Objective. Radiofrequency thermocoagulation (RFT) through the foramen rotundum has emerged as an alternative for treatment of isolated V2 trigeminal neuralgia. But puncture of the foramen rotundum is difficult and time-consuming. In current study, we introduced the application of a computer-assisted design (CAD) template to guide foramen rotundum cannulation. Meanwhile, we assessed its safety and efficacy in the treatment of isolated V2 trigeminal neuralgia. Methods. From November 2015 to August 2017, thirty-eight patients with isolated V2 trigeminal neuralgia were treated with computed tomography- (CT-) guided RFT through the foramen rotundum in our institution. All cases were reviewed, and patients were divided into the experimental group (n=17, puncture with a CAD template) and control group (n=21, free-hand puncture) according to the puncture method used. The puncture times, duration of puncture, and duration of operation were collected. The outcome of pain remission was evaluated utilizing the Barrow Neurological Institute’s (BNI) pain score. Complications and recurrence of pain were also recorded. Data were compared between groups. Results. The rate of one-time successful puncture in the experimental group was obviously higher than that in the control group. Mean puncture times in the experimental group was fewer. Average duration of puncture and operation in the experimental group was also shorter than that in the control group. All patients experienced good pain remission (BNI Class I or II) postoperatively. At four follow-up points (7 days, 3 months, 6 months, and 12 months after operation), there was no significant difference in good pain relief rate between the two groups. Meanwhile, no significant difference was found in complications. Conclusions. CAD template is a safe and precise navigation instrument for RFT treatment of isolated V2 trigeminal neuralgia via the foramen rotundum. Therefore, this novel tool is worthy of clinical promotion.